Ikk2-mediated inflammatory activation of arterial endothelial cells promotes the development and progression of atherosclerosis. (August 2020) - Mussbacher, Marion; Salzmann, Manuel; Haigl, Barbara; Basílio, José; Hochreiter, Bernhard; Gleitsmann, Viola; Moser, Bernhard; Hoesel, Bastian; Suur, Bianca E.; Puhm, Florian; Ungerböck, Caroline; Kuttke, Mario; et al.
Abstract: Background and aims: Inflammatory activation of endothelial cells is considered to be the first step in the development of atherosclerosis. Here, we determined the consequences of chronic endothelial activation via the NF-κB activator Ikk2 (Inhibitor of nuclear factor kappa-B kinase 2, Ikk-beta) on the development and progression of atherosclerosis. Methods: We established a conditional transgenic mouse model, expressing a tamoxifen-inducible, constitutively active form of Ikk2 exclusively in arterial endothelial cells (caIkk2 EC mice) on an ApoE-deficient background. Mice were fed a Western-type diet and endothelial Ikk2 was activated either at early or late stages of atherosclerosis. Results: En face preparations of isolated aortas revealed a significant increase in plaque area in caIkk2 EC mice at 12 weeks of Western-type diet as compared to ApoE-deficient littermates. This was accompanied by increased infiltration of macrophages and T cells into the lesion. Several chemokine/cytokine and immune cell pathways were significantly upregulated in the aortic transcriptome of caIkk2 EC mice. Of note, in mice with established atherosclerosis, activation of endothelial Ikk2 still further accelerated progression of atherosclerosis. This indicates that inflammatory endothelial activation is crucial during all stages of the disease. Conclusions: Our results show for the first time that chronic inflammatory activation of arterial endothelial cells accelerates the development and progression of atherosclerosis both at early and late stages of disease development. Thus, pharmacological targeting of endothelial inflammation emerges as a promising treatment approach. Graphical abstract: Image 1 Highlights: Inflammatory activation of endothelial cells via a constitutively active form of IKK2 in ApoE −/− mice. Inflammatory endothelial activation aggravated atherosclerosis at early and late stages. Endothelial-cell specific inflammation caused phenotypic transitions of smooth-muscle cells.